Tunneling--A Pervasive Vision Disorder. - Getzell, Jeffrey H. (Communique)
Tunneling, a form of exclusive concentration, is a common spatial adaptation. The patient seems to be solely aware of that on which they are centering and block or ignore all other sensory input. It is both a sensory and motor phenomenon that is pervasive in our culture and presents concurrently with all refractive, binocular, and monocular conditions. Tunneling is a common symptom of visual perceiving, processing, and performance issues. Tunneling affects all sensory systems and is caused by physical, physiological, or intellectual/ psychological stress. The symptoms affect how we think, speak, listen, and move. If tunneling is not addressed, it can affect an individual’s ability to see the bigger picture quickly and easily.